Fabrication of SO42--ISE based on Copolymer of Methyl methacrylate-butyl acrylate (MB28) Thin-film and Graphite Pencil Electrode (GPE) - Alva Sagir; Arwati I Gusti Ayu; Hasbullah Siti Aisyah; Aziz Aiman Sajidah Abdul; Khaerudini Deni Shidqi (BIO Web of Conferences)
The SO42- -ISE sensor fabrication process based on MB28 and GPE membranes has been successfully implemented. In this study, the MB28 membrane was prepared using the photo-polymer technique on the surface of a polypyrrole with KCl as a dopant layer previously coated on the GPE surface. In this study, the optimum composition of the MB28 membrane consisted of 1 mg of lipophilic salt TDDACl and a 1:2 mole ratio sulfate ionophore, where the resulting slope approached the Nernstian number with a linear range between 0.1 -10-6 M. Meanwhile, selectivity tests were carried out using the FIM, where SO42--ISE provides good selectivity to I-, Cl- and NO3- ions. This fabricated sensor can work for 12 days at pH 3-9 and provides performance comparable to the gravimetric method according to SNI 19-6964.5-2003.